If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 736 = 4(x + 18) Reorder the terms: 736 = 4(18 + x) 736 = (18 * 4 + x * 4) 736 = (72 + 4x) Solving 736 = 72 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 736 + -4x = 72 + 4x + -4x Combine like terms: 4x + -4x = 0 736 + -4x = 72 + 0 736 + -4x = 72 Add '-736' to each side of the equation. 736 + -736 + -4x = 72 + -736 Combine like terms: 736 + -736 = 0 0 + -4x = 72 + -736 -4x = 72 + -736 Combine like terms: 72 + -736 = -664 -4x = -664 Divide each side by '-4'. x = 166 Simplifying x = 166
| 2y-15=85-3y | | 6r+4=26r+9 | | 9x+42+15x=4y-13 | | 5(-x)-5= | | 0.6x-1=0.5 | | -296=-8(-8x-3) | | (x+8)(2x+4)(3x-6)=0 | | 50x+50x=300 | | 5x+5-5= | | .05(2t-6)=.10(t+4)-.70 | | -4-3(t-5)= | | 2(x-6)=36 | | 8(z+8)= | | 25=45b | | -7+y=34 | | 4(x+2)+2=7x-3(x-2) | | -93=-1 | | tanx-3cotx=0 | | .6x+.7=.9x-.8 | | x+5x+2x=80 | | 30=r-17 | | 10xy=120 | | 4x+-93=-1 | | 1s+1p=15.65 | | 0.8=0.6+x-0.6x | | 64-32x=55-25x | | 3x+2+2x+5=22 | | S-15=12 | | 0.666666667x+3=0.6 | | 0.6+0.7=0.9x-0.8 | | -7c=-35 | | 10+m=13 |